The Proposed Model for Successful Cash Waqf Management for Waqf Institutions in Indonesia - Bahri, Efri Syamsul (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
The collection of cash waqf in Indonesia shows an increase. It is in line with the existence of an agency that explicitly handles waqf in Indonesia, namely the Indonesian Waqf Board (BWI). However, specific research that focuses on the successful management of cash waqf is still limited. This study aims to describe the determinants of the success of cash waqf management. Literature research data sourced from Google Scholar. Data collection using the publish or perish application. Data analysis used the preferred reporting items for systematic reviews and meta-analyses (PRISMA). The study results have identified five indicators of successful cash waqf management: regulation, nadzir, mauquf 'alaih, Islamic financial institutions, and management systems. In the end, this research has also produced a conceptual model that determines the success of cash waqf management. The Indonesian Waqf Board and community organizations that manage cash waqf can respond to the results of this study by increasing their contribution to the five success factors of cash waqf management